Pencegahan Perilaku Agresif Anak Usia Dini dengan Bernyayi dan Menari - Ladya Putri Syafi’i, Aura; Hadi, Dzinnun (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
The purpose of this study was to determine the dynamics of singing and dancing techniques in preventing aggressive behavior in early childhood. This research uses descriptive qualitative research methods. The subjects of the study were students or children who behaved aggressively in PAUD Al-Adiba institutions, Blitar. Data collection was carried out by several methods, namely observation, interviews, and documentation study. The results of the data were analyzed using a grounded theory analysis approach model. The results showed that the aggressive behavior of the children of PAUD Al-Adibal Blitar, among others: beatings, screaming, crying, etc. were caused by factors of parenting, social environment, and genetics. Singing or dancing techniques can be used by teachers in overcoming children's aggressiveness. As much as 80% of early childhood education learning activities are used for singing and dancing for each material. So that singing and dancing can be used as a means of preventing aggressive behavior at PAUD Al-Adiba Blitar from an early age.